Biological features of entomopathogenic fungi strains Beauveria bassiana, perspective for the creation of mycoinsecticides (Experimental biology, 2018)
One of the ways to suppress harmful phytophages is a microbiological method of protection. Entomopathogenic fungi are promising agents of biological control in the fight against insects - pests of agriculture and forestry. Biopreparations, based on entomopathogenic fungi Beauveria bassiana, lead to mass reproduction and distribution resulting in epizootics occurrence. A wide range of biological activity of ascomycete Beauveria bassiana and a safety in relation to animals, humans and plants allows the use of mycoinsecticides based on the fungi in agriculture and forestry. The migratory locust, the Colorado beetle and Ips hauseri are highly sensitive to fungi cultures isolated from the bark beetles. A similar susceptibility to the entomopathogenic fungus Beauveria bassiana is observed among these pests. The main purpose of the work is to assess the biological activity of the studied strains on insects from different systematic groups, as well as the evaluation of mycelial growth in the temperature range of 15-30°C in isolates of the entomopathogenic fungus Beauveria bassiana. Two new strains of Beauveria genus, that have a sufficiently high virulence for test insects, have been selected as a promising producer strains for the production of mycoinsecticides. In addition, temperature preferences are determined for the studied fungal cultures and optimal titers of the working suspension are selected.Key words: entomopathogenic fungi, Beauveria bassiana, virulence, thermotolerance, mycoinsecticide.